THE IMPACT OF DIGITAL TRANSFORMATION PROCESSES ON ENVIRONMENTAL SUSTAINABILITY: OPPORTUNITIES AND RISKS - Shokhistakhon Akhunova; Farangiz A’zamjonova (Ecomind Press, 2025)
The rapid growth of the digital economy is reshaping global production and consumption patterns while creating new environmental challenges and opportunities. This study evaluates the effects of digitalization on energy consumption, carbon emissions, electronic waste generation, and ecological monitoring systems. Using comparative indicators, international datasets, and case-based analysis, the research identifies both the environmental burdens caused by digital infrastructure and the potential of digital technologies—such as artificial intelligence, cloud computing, and the Internet of Things—to enhance resource efficiency and support environmental sustainability. The findings show that while data centers and digital devices increase electricity demand and e-waste volumes, digital solutions significantly improve energy optimization, pollution monitoring, and waste management.
Keywords: Digital economy, environmental impact, e-waste, green technologies, energy consumption, sustainability, IoT.